Residential cookstove emissions: measurement and modeling from the lab and field - Bilsback, Kelsey, author; Volckens, John, advisor; Barnes, Elizabeth, committee member; Jathar, Shantanu, committee member; Marchese, Anthony, committee member; Pierce, Jeffrey, committee member (Colorado State University. Libraries, 2018)
Emissions from solid-fuel cookstoves, which result from poorly controlled combustion, have been linked to indoor and outdoor air pollution, climate forcing, and human disease. The adverse effects of cookstoves have motivated commitment of substantial time and resources towards development of "improved" cookstoves that operate more efficiently and reduce emissions of harmful air pollutants. However, once disseminated to cookstove users, improved cookstoves often do not ameliorate air quality to a level that substantially reduces health risks or negative environmental impacts. Several critical knowledge gaps related to the emissions and performance of "improved" cookstoves exist; attempting to address these gaps is the subject of this dissertation. Widely-used laboratory testing protocols overestimate the ability of improved stoves to lower emissions. In this work, we develop and validated a novel laboratory test protocol entitled the Firepower Sweep Test. We find that the Firepower Sweep Test reproduces the range of PM2.5 and CO emissions observed in the field, including high emissions events not typically observed under current laboratory protocols. We also find that firepower is modestly correlated with emissions, although this relationship depends on stove-fuel combination. Our results justify incorporating multiple-firepower testing into laboratory-based protocols, but demonstrate that firepower alone cannot explain the observed variability in cookstove emissions. Cookstoves emit many pollutants; however, most studies only measure fine particulate matter (PM2.5) and carbon monoxide (CO). In this work, we present an extensive inventory of air pollutants emitted from wood, charcoal, kerosene, and liquefied petroleum gas (LPG) cookstoves. One-hundred and twenty pollutants, including PM2.5, CO, organic matter, elemental carbon, inorganic ions, carbohydrates, ultrafine particles, volatile organic compounds, carbonyls, and polycyclic aromatic hydrocarbons, are included in this inventory. Our results demonstrate that, while most improved stoves tend to reduce PM2.5 and/or CO emissions, reductions PM2.5 and/or CO emissions do not always correspond to reductions of other harmful pollutants. These findings highlight the need to characterize the full emissions profile of "improved" cookstove designs before they are disseminated to users. Accurate emissions data are critical inputs for models that aim to quantify the impacts of cookstoves on climate and health. Currently, model inputs are primarily derived from laboratory experiments that do not represent in-home use. In this work, we present a relatively inexpensive technique that uses a temperature measurement made at the combustion chamber outlet to estimate firepower. These firepower estimations have the potential to provide valuable information about the range of firepowers over which cookstoves are operated at during real-world use. We also demonstrate that in-use firepower measurements from "improved" cookstoves can be combined with laboratory emissions data from the Firepower Sweep Test to estimate in-use emissions using linear regression models. We find that the model predictions are accurate enough to determine which International Standards Organization emissions tier a given "improved" stove is likely to fall under.